Big red lollipop - Khan, Rukhsana, 1962- (Viking, 2010)
Having to take her younger sister along the first time she is invited to a birthday party spoils Rubina's fun, and later when that sister is asked to a party and baby sister wants to come, Rubina must decide whether to help.